2020
DOI: 10.1155/2020/5343014
|View full text |Cite
|
Sign up to set email alerts
|

Diverse Associations of Plasma Selenium Concentrations and SELENOP Gene Polymorphism with Metabolic Syndrome and Its Components

Abstract: The relationship between selenium and metabolic syndrome (MetS) has been discussed controversially, and limited studies have examined the associations of single nucleotide polymorphisms in selenoproteins genes with MetS. Hence, to examine the associations of plasma selenium concentrations and selenoprotein P rs7579 polymorphism with MetS, a case-control study of 1279 MetS cases and 1279 sex- and age- (±2 years) matched controls was conducted based on the baseline data of the Tongji-Ezhou Cohort study. Plasma s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 45 publications
0
22
1
Order By: Relevance
“…This was the case despite the overall amount of selenium exposure falling in the expected range for both the Italian and more generally the European populations [ 21 , 26 , 49 ], and despite the fact that these associations were weak and generally statistically imprecise. The possibility that selenium may increase glycemia has been suggested by some prospective [ 50 , 51 ] and cross-sectional or case-control studies [ 50 , 52 , 53 , 54 ], although not all cohort studies are consistent [ 6 , 55 ]. In addition, a positive association between selenium exposure and glycemia is strongly supported by experimental and non-experimental studies on selenium and type 2 diabetes, with randomized controlled trials consistently showing a relation between selenium supplementation and disease risk [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was the case despite the overall amount of selenium exposure falling in the expected range for both the Italian and more generally the European populations [ 21 , 26 , 49 ], and despite the fact that these associations were weak and generally statistically imprecise. The possibility that selenium may increase glycemia has been suggested by some prospective [ 50 , 51 ] and cross-sectional or case-control studies [ 50 , 52 , 53 , 54 ], although not all cohort studies are consistent [ 6 , 55 ]. In addition, a positive association between selenium exposure and glycemia is strongly supported by experimental and non-experimental studies on selenium and type 2 diabetes, with randomized controlled trials consistently showing a relation between selenium supplementation and disease risk [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…The association of adverse lipid profile endpoints with urinary selenium is not entirely surprising, given the dose–response association between higher blood selenium concentrations and metabolic syndrome, higher triglycerides and LDL-cholesterol, as well as the lower HDL-cholesterol consistently found in the National Health and Nutrition Examination Surveys (NHANES) and other studies [ 39 , 52 , 54 , 56 , 57 , 58 ]. Conversely, randomized controlled trials have shown little if any effect of selenium supplementation on the lipid profile [ 38 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…The current study was conducted based on the Tongji-Ezhou (TJEZ) cohort study, which is an ongoing prospective cohort study, with the aim of investigating the associations of lifestyle, dietary factors, and genetic factors with chronic diseases. Design of the TJEZ cohort study has been described elsewhere ( 5 ). Briefly, 5,533 residents in Ezhou aged above 20 years were recruited between 2013 and 2015.…”
Section: Methodsmentioning
confidence: 99%
“…Plasma selenium concentrations were measured by inductively coupled plasma mass spectrometry (Agilent 7700 Series, Tokyo, Japan) in the Ministry of Education Key Laboratory of Environment and Health at Tongji Medical College of Huazhong University of Science & Technology, as described previously ( 5 ). Prior to analysis, thawed samples (40 μL plasma) were diluted with ultrapure water and digestive solution at a ratio of 1:19:20.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation